Analysis of cupuaçu dairy drink (Research, Society and Development, 2020)
The dairy drink is a derivative made with milk and whey, which can be fermented or not, plus other food ingredients, such as fruit pulps, cream and vegetable fats. Of great acceptance in the market, the dairy drink is very nutritious and, currently, it has been considered as a way to reuse the serum, in liquid form, in addition to avoiding environmental pollution. The work aimed to develop and sensorially evaluate three formulations of cupuaçu non-fermented milk drink with different concentrations of whey and whole milk powder. The sensory analysis demonstrated good acceptance among the three formulations of the milk drink and that high amounts of powdered milk does not improve the sensory properties of the final product. The results also proved to be a low-cost product by reusing whey from dairy products, reaching the final consumer as a differentiated product with added value.